Comparison of spontaneous eruption and modified closed eruption technique with palatal traction in alignment of impacted maxillary central incisor teeth - Ivo Marek; Anna Janková; Martin Starosta; Michal Novosad; Josef Kučera (SpringerOpen, 2023)
Abstract Background Central incisor impaction is a rare condition with potentially severe clinical and psychological implications for the patient. Treatment techniques vary according to the pretreatment situation and individual factors. The aim of this study was to compare the esthetic outcomes and treatment times between two different approaches. Materials and methods In this retrospective study, thirty-one consecutive patients (13 boys, 18 girls; average age 9.5 ± 2.3 years) with a total of 34 impacted permanent upper central incisors were included in the study. Patients were divided into two groups according to method of treatment. Group A comprised patients in whom spontaneous eruption occurred after space opening (n = 12), and Group B comprised patients in whom teeth showed no eruption and required treatment with a modified closed eruption method with palatally oriented traction (n = 19). Treatment time and esthetic outcomes were assessed and compared between groups. Results The mean treatment time was 22.0 ± 6.7 months, and all teeth were successfully aligned. No statistically significant difference in average treatment time was found between groups in baseline characteristics (p > 0.05). The amount of attached gingiva was significantly smaller when compared to contralateral reference teeth in the closed eruption group (Group B; p = 0.03). However, no difference in amount of attached gingiva was found between both groups (p = 0.26). Additionally, no difference in the clinical crown length was found between groups (p = 0.27). Conclusion The closed eruption method with palatal traction directed at the peak of the alveolar crest provided results comparable to the physiologic tooth eruption.